2015
DOI: 10.1097/cad.0000000000000242
|View full text |Cite
|
Sign up to set email alerts
|

S-1 combined with cisplatin versus cisplatin alone for the treatment of advanced gastric cancer

Abstract: We aimed to assess the efficacy and safety of S-1 combined with cisplatin (SC) over cisplatin alone (C) for the treatment of advanced gastric cancer in China. Between July 2009 and June 2011, 72 eligible patients with advanced gastric cancer were selected and divided randomly into two groups. Thirty-six patients received SC, with S-1 on days 1 through 14 of a 21-day cycle and cisplatin (60 mg/m on day 1) every 4 weeks for two cycles. The other 36 patients were administered only cisplatin (in the same manner as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Of the 18 reports remaining for full-text reading, 3 studies were eligible to assess SC versus 5-Fu plus cisplatin, 1 study was eligible to assess SC versus cisplatin alone, 2 studies were eligible to assess SC versus S-1 combined with oxaliplatin or leucovorin, and 2 studies were eligible to assess SC versus S-1, cisplatin combined with other treatment (i.e., TSU68, leucovorin). Following the inclusion and exclusion criteria, 8 RCTs [8,11–17] consisting of 2699 AGC patients were selected and included in this meta-analysis. Detailed information about the flow chart of study selection process is reported in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 reports remaining for full-text reading, 3 studies were eligible to assess SC versus 5-Fu plus cisplatin, 1 study was eligible to assess SC versus cisplatin alone, 2 studies were eligible to assess SC versus S-1 combined with oxaliplatin or leucovorin, and 2 studies were eligible to assess SC versus S-1, cisplatin combined with other treatment (i.e., TSU68, leucovorin). Following the inclusion and exclusion criteria, 8 RCTs [8,11–17] consisting of 2699 AGC patients were selected and included in this meta-analysis. Detailed information about the flow chart of study selection process is reported in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the demographic characteristics of included trials were generally comparable. Several studies might introduce potential heterogeneity owing to incompatible baseline features with other studies, such as recruiting elderly patients (>70 years old), 12,[29][30][31][32] containing esophageal, [13][14][15]29,31,[33][34][35][36] fake registration identifier, 37 nonmeasurable cases only, 38 and peritoneal metastasis only 39 (Table 1). The influence on pooled results by these studies was further detected in sensitivity analysis.…”
Section: General Analysis: Baseline Features and Transitivitymentioning
confidence: 99%